TLR4 Signaling and Heme Oxygenase-1/Carbon Monoxide Pathway Crosstalk Induces Resiliency of Myeloma Plasma Cells to Bortezomib Treatment - Grazia Scandura; Cesarina Giallongo; Fabrizio Puglisi; Alessandra Romano; Nunziatina Laura Parrinello; Tatiana Zuppelli; Lucia Longhitano; Sebastiano Giallongo; Michelino Di Rosa; Giuseppe Musumeci; Roberto Motterlini; Roberta Foresti; et al. (MDPI AG, 2022)
Relapse in multiple myeloma (MM) decreases therapy efficiency through unclear mechanisms of chemoresistance. Since our group previously demonstrated that heme oxygenase-1 (HO-1) and Toll-like receptor 4 (TLR4) are two signaling pathways protecting MM cells from the proteasome inhibitor bortezomib (BTZ), we here evaluated their cross-regulation by a pharmacological approach. We found that cell toxicity and mitochondrial depolarization by BTZ were increased upon inhibition of HO-1 and TLR4 by using tin protoporphyrin IX (SnPP) and TAK-242, respectively. Furthermore, the combination of TAK-242 and BTZ activated mitophagy and decreased the unfolded protein response (UPR) survival pathway in association with a downregulation in HO-1 expression. Notably, BTZ in combination with SnPP induced effects mirroring the treatment with TAK-242/BTZ, resulting in a blockade of TLR4 upregulation. Interestingly, treatment of cells with either hemin, an HO-1 inducer, or supplementation with carbon monoxide (CO), a by-product of HO-1 enzymatic activity, increased TLR4 expression. In conclusion, we showed that treatment of MM cells with BTZ triggers the TLR4/HO-1/CO axis, serving as a stress-responsive signal that leads to increased cell survival while protecting mitochondria against BTZ and ultimately promoting drug resistance.